2019
DOI: 10.1177/0734904119849395
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intumescent mat on post-fire performance of carbon fibre reinforced composites

Abstract: This study investigated the effect of intumescent mats (M1 and M2) with different compositions on the post-fire performance of carbon fibre reinforced composites (CFRP). The sandwich structure was designed for composites where M1 (CFRP-M1) or M2 (CFRP-M2) mats were covered on the composite surface. A significant reduction in the peak heat release rate (PHRR) and total heat release (THR) was observed from the cone calorimetric data and CFRP-M1 composite showed the lowest value of 148 KW/m 2 and 29 MJ/m 2 for PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…After 5% alkali and 5% silane treatment, the LOI values of composites increase, which is 22.4% and 23.5%, respectively. [ 52‐55 ] This can be attributed to the same phenomenon as explained in previous section. The chemical modifications with alkali and silane treatment have improved the interfacial adhesion between the fiber‐matrix interface.…”
Section: Resultssupporting
confidence: 65%
“…After 5% alkali and 5% silane treatment, the LOI values of composites increase, which is 22.4% and 23.5%, respectively. [ 52‐55 ] This can be attributed to the same phenomenon as explained in previous section. The chemical modifications with alkali and silane treatment have improved the interfacial adhesion between the fiber‐matrix interface.…”
Section: Resultssupporting
confidence: 65%
“…During this process, not all the developed gas pressure is liberated, resulting from the gas permeability of the composites. As such, internal pressure develops leading to the expansion of the composite, resulting in delamination cracks and gas-filled pores, rapid creeping, buckling, and various other composite failures under heat conditions [21,[42][43][44]. This process continues until all the composite has been converted into volatiles, smoke, soot, and char.…”
Section: Thermal Mechanisms Of Fibre-reinforced Compositesmentioning
confidence: 99%
“…Whilst existing studies examining the post-fire mechanical behaviour of CFRP laminates have shown that the reduction in the post-fire mechanical properties can be attributed to thermal degradation and damage caused by the heat from a fire, these studies were restricted to measuring the post-fire behaviour of CFRP containing a single fibre orientation [17][18][19][20] without comparing this behaviour to other commonly used fibre orientations, even though the mechanical properties of CFRP laminates are heavily dependent on the type of fibre orientation. 21,22 Furthermore, in studies investigating fibre orientation on post-fire behaviour, only one study, to the author's knowledge, has been carried out in tension, 20 with no study evaluating the influence of fibre orientation on post-fire bending behaviour.…”
Section: Existing Studiesmentioning
confidence: 99%